The short-term effects of the postnatal use of corticosteroids in the prevention and treatment of bronchopulmonary dysplasia in preterm infants - Stouppa, Katerina (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Introduction: Bronchopulmonary Dysplasia, a type of chronic lung disease, is a common complication in premature infants. Corticosteroids, as anti-inflammatory drugs, can be used for the prevention or treatment of Bronchopulmonary Dysplasia (BPD). Despite their effectiveness, the use of corticosteroids has become a center of dispute, due to the side effects associated with them. Aim: The aim of this study was to review the academic literature related to the short term effects of the use of Corticosteroids for the prevention and treatment of BPD Material and method: A critical review of the literature published between 2003 –2013 was performed. Literature collection was performed by the use of PubMed, Cinahl, Medline and Science Direct databases. Filtering of results was done by following key-words: Bronchopulmonary Dysplasia, postnatal corticosteroids, premature or preterm infants. Results: Ten studies were included which med the criteria. Infants had a mean Gestational Age range of 24 to 29.6 weeks and with mean Birth Weight range 652 to 1092g, all on mechanical ventilator. Three types of corticosteroids were investigated (Dexamethasone, Hydrocortisone, and Betamethasone). The short-term effects of the using corticosteroids vary, depending on the specific medication employed, dosage and time. The beneficial effects on premature infants were lower mortality and morbidity rate, lower incidence of Bronchopulmonary Dysplasia (BPD), facilitating extubation and better ventilation score. Short side effects include reduction of Growth, Intestinal Perforation, Total Cerebral and Cortical Tissue, lower Motor Optimality Score (MOS), impaired General Movements (GMs), Periventricular Leykomalacia (PVL), Intraventicular Hemorrhage (IVH) & Retinopathy of Prematurity (ROP) Conclusions: Corticosteroid treatment in prematurity for treatment or prevention of Bronchopulmonary Dysplasia has many beneficial results, but at the same time is associated with many short – term side effects. Very selective treatment for the highest risk infants with low dose of corticosteroid for as much short as possible duration, after the first week of life is safer.
Keywords: Bronchopulmonary Dysplasia; Postnatal corticosteroids; Premature; Preterm; Infants